EXTENDED SESSION OF THE SCIENCE AND METHODOLOGY PANEL ON THE FORENSIC ANALYSIS OF CONSUMER GOODS: !FORENSIC EXAMINATION OF FOOD PRODUCTS FOR EVALUATION AND OTHER PURPOSES" #RFCFS OF THE RUSSIAN MINISTRY OF JUSTICE, DECEMBER 4$5, 2013% - A. Selivanov (Теория и практика судебной экспертизы, 2014)
.